The Impact of the Registration System Reform on Corporate ESG Ratings: An Empirical Analysis Based on Public Data from the Growth Enterprise Market - Lu Guanzhi; Gu Ran; Zhang Xinyue (SHS Web of Conferences)
Using public data from GEM listed companies from 2015 to 2022 as research samples, the author performs an empirical test in this paper. The impact of registered restructuring on the ESG performance of GEM enterprises is investigated, and the dependent variable is replaced with a multiple regression model, grouped regression, and endogeneity test instead of the robustness test. Research findings: Institutional investors’ IPO shares skyrocketed when the GEM registration procedure was redesigned, which significantly improved the firms’ ESG performance. The ESG scores of low- carbon firms have significantly improved, and the “reform of the registration system” has the potential to enhance the overall ESG score of enterprises in developed coastal urban areas. The author provides an in-depth analysis of how the GEM registration system influences enterprise ESG ratings, suggesting that reforming this system could lead to better ESG performance among businesses. Furthermore, the author presents both theoretical and empirical justifications for reforming the comprehensive registration system within China’s capital market by exploring the internal mechanisms through which changes to the GEM enrolment system impact enterprise ESG ratings from a unique perspective.